Perancangan kursi duduk-berdiri berdasarkan pendekatan antropometri di PT. Otscon Safety Indonesia - Rizki Fitrian (Institut Seni Indonesia Yogyakarta, 2021)
The problem of incompatibility between facilities and humans is still found, where the impact is the insecurity of worker safety, increased workload, disruption of work processes, and their effects on workers' conditions. PT. Otscon Safety Indonesia is a manufacturing company that manufactures automotive components called the Lever Parking Brake. The company has an assembly work station called Button Release Assy, where the work is done in a standing work position, so that operators will quickly feel fatigue from working in a standing position.This study aims to design a Sit-and-Stand Chair, so that operators working at the button release work station do not experience fatigue quickly. The design of the Sit-and-Stand Chair is based on the Anthropometric approach to create an ergonomic chair. The size of the chair is determined based on the results of the percentile calculation of body dimensions, where the body dimensions used are the hip width to find the diameter of the seat cushion and hip height and the vertical height of the chair from the floor. The results showed that the chair seat diameter from the 95th percentile was ∅35.4 cm and the height of the chair from the floor vertically from the 5th percentile was 83.4 cm